Assessment of Interventional Strategies for Reducing Test and Mathematics Anxiety among Early Childhood Care Education Pre-Service Teachers in Imo State - UNAMBA, Eugene Chukwuemeka; EWUNONU, Nkechi Ngozi; UGOCHUKWU, Ngozi; OGUOMA, Chinyere (Ilorin Journal of Education, 2024)
The study assesses interventional strategies for reducing test and mathematics anxiety among early childhood care education pre-service teachers in tertiary institution. Based on the objectives of the study one research question and one hypothesis were formulated. Descriptive survey research design was used and the population of the study was 468 teacher educators. Simple random sampling technique was used to select 414 comprising of 116 males and 298 females. The instrument for data collection was a structured questionnaire titled assessment of interventional strategies for reducing test and mathematics anxiety among early childhood care education pre-service teachers in tertiary institution (AISRTAPT). The AISRTAPT was validated by two experts in psychology education and one expert in measurement and evaluation while the reliability of the AISRTAPT were determined using cronbach alpha reliability which yielded 0.85 coefficient. Data collected were analyzed using mean and standard deviation for research question. The study indicated interventional strategies for reducing test anxiety and mathematics anxiety irrespective of gender. It was recommended that workshops should be organized for Mathematics and teacher educators to known interventional strategies for reducing test anxiety and mathematics anxiety among pre-service teachers.